Is there a direct solar proton impact on lower stratospheric ozone? - Jia, Jia; Kero, Antti; Kalakoski, Niilo; Szeląg, Monika E.; Verronen, Pekka T. (2020)
We investigate Arctic polar atmospheric ozone responses to Solar Proton Events (SPEs) using MLS satellite measurements (2004–now) and WACCM-D simulations (1989–2012). Special focus is on lower stratospheric ozone depletion that has been proposed earlier based on superposed epoch analysis of ozonesonde anomalies (up to 10 % ozone decrease). Superposed Epoch Analysis (SEA) of the satellite dataset provides no evidence of any average SPE impact on the lower stratospheric ozone, although at the mesospheric altitudes a statistically significant ozone depletion is present. In the individual case studies, we find only one potential case (January 2005) in which the lower stratospheric ozone level was significantly decreased after the SPE onset. However, similar decreases could not be identified in other SPEs of similar or larger magnitude. We find a very good overall consistency between SPE-driven ozone anomalies derived from the WACCM-D model simulations and the Aura MLS data. The simulation results before the Aura MLS era indicate no significant effect on the lower stratospheric ozone either. As a conclusion, the SPE has a zero direct impact on the lower stratospheric ozone.